The R-U5-5' leader sequence of neurovirulent wild mouse retrovirus contains an element controlling the incubation period of neurodegenerative disease. - Portis, J L (1991)
The wild mouse ecotropic retrovirus CasBrE causes a spongiform neurodegenerative disease after neonatal inoculation, with an incubation period ranging from 2 to 12 months. We previously showed that introduction of long terminal repeat (LTR) and gag-pol sequences from a strain of Friend murine leukemia virus (FB29) resulted in a dramatic acceleration of the onset of the disease. The chimeric virus FrCasE, which consisted of the FB29 genome containing 3' pol and env sequences from the wild mouse virus, induced a highly predictable, lethal neurodegenerative disease with an incubation period of only 16 days. Here we report that the sequences which are primary determinants of the length of the incubation period are located in the 5' end of the viral genome between a KpnI site in the R region of the LTR and a PstI site immediately 5' of the start codon for pr65gag (R-U5-5' leader). This region contains the tRNA primer binding site, splice donor site for the subgenomic env mRNA, and the packaging sequence. Computer-assisted sequence analysis failed to find evidence of a consensus sequence for a DNA enhancer in this region. In addition, sequences within a region of the genome between a ClaI site at the 3' end of env to the KpnI site in the R region of the LTR (inclusive of U3) also influenced the incubation period of the disease, but the effect was distinctly weaker than that of the R-U5-5' leader sequence. This U3 effect, however, appeared to be independent of the number of direct repeats, since deletion of one of two duplicated 42-base repeats containing consensus sequences of nuclear-factor binding domains had no effect on the incubation period of the disease. On the basis of Southern blot analysis of total viral DNA in the tissues, the effect of these sequences on the incubation period appeared to be related to the level of virus replication in the central nervous system. All of the chimeric viruses analyzed, irrespective of neurovirulence, replicated to comparable levels in the spleen and induced comparable levels of viremia.